Calculating germinal centre reactions. Issue 18 (December 2019) - Buchauer, Lisa; Wardemann, Hedda
Abstract: Germinal centres are anatomically defined lymphoid organ structures that mediate B-cell affinity maturation and affect the quality of humoral immune responses. Mathematical models based on differential equations or agent-based simulations have been widely used to deepen our understanding of the cellular and molecular processes characterising these complex dynamic systems. Along with experimental studies, these tools have provided insights into the spatio-temporal behaviour of B-cells in germinal centre reactions and the mechanisms underlying their clonal selection and cellular differentiation. More recently, mathematical models have been used to define several key parameters that influence the quality of humoral vaccine responses such as vaccine composition and vaccination schedule. These studies generated testable predictions for the design of optimised immunisation strategies. Graphical abstract: Basic structure and applications of germinal centre simulations. Image 1